2017
DOI: 10.1038/srep42298
|View full text |Cite
|
Sign up to set email alerts
|

An air-liquid interphase approach for modeling the early embryo-maternal contact zone

Abstract: We developed an air-liquid interphase culture procedure for mammalian oviduct epithelial cells leading to the formation of functional epithelial tissues, which generate oviduct fluid surrogates. These in vitro oviduct epithelia can be co-cultured with living zygotes and enable embryonic development up to the blastocyst stage without addition of embryo culture medium. The described strategy is broadly applicable to analyze early embryo-maternal interactions under standardized in vitro conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 16 publications
2
61
0
3
Order By: Relevance
“…Air‐liquid interface models allow acquisition and analysis of both the apical/luminal fluid created by the epithelia and the conditioned basolateral medium. It has been shown that ALI‐derived oviductal fluid surrogates share apparent similarities to oviductal fluid in vivo (Chen et al., ; Simintiras et al., ). As estrous cycle dependent changes in the epithelium can be mimicked by application of progesterone and estradiol to the basal compartment (Chen et al., 2013a, ), they can also be employed to investigate the dynamic, steroid‐driven modifications in the fluid composition during the peri‐conceptional period.…”
Section: Application Of Ali Cultures For Reproductive Biology and Assmentioning
confidence: 99%
See 3 more Smart Citations
“…Air‐liquid interface models allow acquisition and analysis of both the apical/luminal fluid created by the epithelia and the conditioned basolateral medium. It has been shown that ALI‐derived oviductal fluid surrogates share apparent similarities to oviductal fluid in vivo (Chen et al., ; Simintiras et al., ). As estrous cycle dependent changes in the epithelium can be mimicked by application of progesterone and estradiol to the basal compartment (Chen et al., 2013a, ), they can also be employed to investigate the dynamic, steroid‐driven modifications in the fluid composition during the peri‐conceptional period.…”
Section: Application Of Ali Cultures For Reproductive Biology and Assmentioning
confidence: 99%
“…Air‐liquid interface‐based in vitro models of FRT epithelia can be used to culture living zygotes (Chen et al., ; Ferraz, Henning, Costa, et al., ; Ferraz et al., ). Murine, porcine, as well as bovine zygotes grown within the apical compartment of oviduct ALI systems developed up to the blastocyst stage without any addition of embryo culture medium (Chen et al., ). First results showed that the marker gene expression of bovine embryos cultured on ALI oviduct epithelia is not largely different from that of embryos produced via standard in vitro procedures.…”
Section: Application Of Ali Cultures For Reproductive Biology and Assmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the technical, and often ethical, limitations surrounding in vivo sampling, one direction towards addressing this includes in vitro modelling. Advances have been made regarding the production of bovine in vitro derived oviduct fluid (ivDOF) which resemble in vivo derived fluid and moreover supports early embryo development (Chen et al, 2017), however, this can be considered currently under optimisation and has yet to be recapitulated to the uterus. The delay in an in vitro uterine luminal fluid (ivULF) is partly attributable to the increased complexity of the endometrium, notably the presence of glands and a greater number of different cell types.…”
Section: Additional Considerationsmentioning
confidence: 99%